Modern container architecture - Hart, Aidan (Images Publishing, 2016)
Container architecture is one of the most sustainable building types in the modern day world. It is already widely used in many countries. Architects and artists incorporate containers' unique aesthetic value to house various functions, such as stores, exhibitions, museums, and houses. In recent years, designers in China have begun to pay close attention to this construction field, and more and more creative container houses are being built in big cities. This book contains many excellent cases, showing readers the unique charm of modern container architecture.